Optimizing portfolio performance in indonesian banking stocks: An empirical application of the markowitz mean-variance framework - Pulungan, Ahmad Fauzan; Riri Syafitri Lubis (Desimal: Jurnal Matematika, 2025)
This study aims to construct an optimal investment portfolio in Indonesia’s banking sector using the Mean-Variance Markowitz approach. Employing a quantitative descriptive method, the research analyzes monthly closing stock prices of 10 banking companies listed on the Indonesia Stock Exchange from January to December 2024. Data processing was conducted using Microsoft Excel, including return calculation, risk measurement through standard deviation, covariance matrix formation, and portfolio optimization via the Sharpe Ratio. The findings reveal that the optimal portfolio consists of BRIS and PNBN stocks, achieving the highest Sharpe Ratio of 0.6639, which reflects a well-balanced risk-return profile. Conversely, the minimum-risk portfolio yielded a negative return, highlighting that lower risk does not always translate to profit. These results affirm the effectiveness of the Markowitz model in supporting rational investment decision-making, particularly for young investors.